Design of an Information System for Quantitative and Qualitative Analysis of Patient Medical Records at Puskesmas XYZ - Andes Nanda Pratama (SMART : Jurnal Teknologi Informasi dan Komputer, 2025)
The quantitative and qualitative analysis of medical records is a critical component of medical record management that ensures the completeness, accuracy, and consistency of patient health data in primary healthcare facilities. However, this process at Puskesmas XYZ is still conducted manually using paper forms, resulting in slow processing times, high risk of error, and difficulty in compiling aggregate reports. This research designs a web-based information system for quantitative and qualitative analysis of patient medical records using the Systems Development Life Cycle (SDLC) method with the Waterfall model. The system is built using the PHP CodeIgniter 4 framework, MySQL database, and a Bootstrap-based interface. The quantitative analysis module covers four review components: identification, authentication, recording, and reporting. The qualitative analysis module covers two components: consistency diagnosis and recording procedures. System evaluation was conducted using the ISO 25010 quality standard covering six characteristics: functional suitability, performance efficiency, usability, reliability, security, and maintainability. Testing results show an overall system quality score of 83.7% (Very Good category). The system successfully reduces medical record analysis time by 67.4% compared to manual methods and increases the completeness rate of medical record documentation from 71.3% to 94.8%. The novelty of this research lies in the integration of an automated completeness checklist module with a real-time incomplete medical record (IMR) tracking dashboard, which has not previously been developed specifically for the primary healthcare (Puskesmas) context in Indonesia.